Response surface modeling of photogenerated charge collection of silver-based plasmonic dye-sensitized solar cell using central composite design experiments - Samaila, Buda; Shafie, Suhaidi; Abdul Rashid, Suraya; Jaafar, Haslina; Abdgalil, Ali Khalifa (Elsevier, 2017)
In this study, silver nanoparticles (AgNP) have been prepared and successfully incorporated in TiO2 nanopowder and used in dye-sensitized solar cell as photoanode. The effect of the AgNP concentration and photoanode film thickness on the charge collection efficiency of a photogenerated electron at the external circuit was investigated using response surface methodology. A multiple regression analysis of second order polynomial was employed to fit the experimental data and an empirical model was subsequently developed using analysis of variance (ANOVA). The results show that two independent variables (AgNP concentration and photoanode film thickness) have significantly influenced the charge collection efficiency of the silver-based plasmonic DSSC. An optimum charge collection of 64.3% was obtained at AgNP concentration and film thickness of 5%wt and 10 μm, respectively.